Monozygotic Pregnancies Following Assisted Reproductive Technology: A Review - Mariano Mascarenhas; Keerthi Gnanaprabha (European Medical Journal, 2016)
Introduction: Assisted reproductive technology (ART) is associated with an increased risk of monozygotic twinning. This narrative review attempts to summarise the known literature regarding the aetiology, incidence, risk factors, diagnosis, and prognosis of monozygotic twinning following ART. Aetiology: Monozygotic twinning is caused by the splitting of the early embryo during the peri-implantation phase. According to the classical hypothesis, the timing of the split determines the chorionicity and amnionicity, however this has been questioned in recent literature. Incidence and risk factors: The incidence of monozygotic twinning in natural conception appears to be independent of extrinsic factors such as ethnicity and age. The incidence of monozygotic twinning is increased from 0.4% of natural conceptions to around 0.9-2.24% of pregnancies following ART. The available literature supports a role of ovarian stimulation and extended culture to the blastocyst stage in increasing the risk of monozygotic twinning. The impact of maternal age and micromanipulation techniques such as assisted hatching and intra-cytoplasmic sperm injection appear to depend on the stage of the embryo being transferred leading to significant heterogeneity between studies. Diagnosis: The gold standard for diagnosing monozygotic twinning is genetic testing but its cost precludes it from routine widespread use. Most epidemiological studies utilise statistical estimates such as Weinberg's differential rule and tailored questionnaires. Most studies from ART units have utilised transvaginal sonography for counting the number of gestational sacs or assessing the chorionicity. Prognosis: The prognosis of twins appears to be dependent on the chorionicity and amnionicity and is largely independent of the zygosity.